2004
DOI: 10.1139/z04-098
|View full text |Cite
|
Sign up to set email alerts
|

Sex and species differences in plasma oxytocin using an enzyme immunoassay

Abstract: The neuropeptide hormone oxytocin (OT) is released peripherally and centrally and has been implicated in both physiology and behavior, especially sociosexual behaviors. Knowledge of OT levels in blood or other sources would be useful but these are rarely reported. Radioimmunoassay following extraction is the most commonly used method for measuring OT but is not ideal for use in small mammals in which blood volumes and concentrations of OT are low. Here we report a chemical and biological validation for a comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 51 publications
3
71
1
Order By: Relevance
“…Samples were assayed in duplicate; the intra-assay and inter-assay coefficients of variation were under 10%. The assay has been validated (Carter et al, 2007;Kramer, Cushing, Carter, Wu, & Ottinger, 2004), and this protocol has been used extensively (Ebstein, Knafo, Mankuta, Chew, & Lai, 2012) with stable individual values (Gouin et al, 2010;Weisman, Zagoory-Sharon, Schneiderman, Gordon, & Feldman, 2013). The OT values in the present sample fall within the range reported in other samples of pregnant women using this protocol (Prévost et al, 2014).…”
Section: Methodssupporting
confidence: 67%
“…Samples were assayed in duplicate; the intra-assay and inter-assay coefficients of variation were under 10%. The assay has been validated (Carter et al, 2007;Kramer, Cushing, Carter, Wu, & Ottinger, 2004), and this protocol has been used extensively (Ebstein, Knafo, Mankuta, Chew, & Lai, 2012) with stable individual values (Gouin et al, 2010;Weisman, Zagoory-Sharon, Schneiderman, Gordon, & Feldman, 2013). The OT values in the present sample fall within the range reported in other samples of pregnant women using this protocol (Prévost et al, 2014).…”
Section: Methodssupporting
confidence: 67%
“…2.1.5 Circulating Hormone and Peptide Analysis-Plasma levels of oxytocin were determined using a commercially available enzyme-linked immunosorbent assay kit (Assay Designs, Ann Arbor, MI), which has been validated previously for use in prairie voles (Kramer et al, 2004). Inter-and intra-assay coefficients of variation for oxytocin are 10.0% and 10.5%, respectively.…”
Section: 14mentioning
confidence: 99%
“…We note that the range of OT levels that was measured in the current study is according to the levels observed for Sprague-Dawely rats, measured by enzyme-linked immunoassay. 32 Leptin. Samples were diluted 1:11 in the assay buffer and treated according to the instructions of the commercial kit.…”
Section: Tissue Collectionsmentioning
confidence: 99%